CFD Analysis and Electrical Efficiency Improvement of a Hybrid PV/T Panel Cooled by Forced Air Circulation - et. al., Alok Kumar Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Renewable energy sources are becoming more and more popular, regarding the pollution and non-sustainability of common energy sources. The study mainly focused on the improvement of the PV collector performance by using ANSYS fluent. The design of the fin will change according to the previous study. In the current study, we will increase the thermal contact area of the fin by changing the design of the fin. The change in the design of the fin will increase the total heat transfer and efficiency of the system. It concluded that with better-designed fin arrangements, the required fan speed could be lowered for any number of fins or similar results could be obtained with fewer fins. On the other hand, since the power required by the PV-powered fan will also decrease with fewer fins and at lower air velocities, the total efficiency obtained from the PV system will also increase.